2023
DOI: 10.1001/jamaoncol.2022.7949
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alisertib Alone or Combined With Fulvestrant in Patients With Endocrine-Resistant Advanced Breast Cancer

Abstract: ImportanceAurora A kinase (AURKA) activation, related in part to AURKA amplification and variants, is associated with downregulation of estrogen receptor (ER) α expression, endocrine resistance, and implicated in cyclin-dependent kinase 4/6 inhibitor (CDK 4/6i) resistance. Alisertib, a selective AURKA inhibitor, upregulates ERα and restores endocrine sensitivity in preclinical metastatic breast cancer (MBC) models. The safety and preliminary efficacy of alisertib was demonstrated in early-phase trials; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Interestingly, anti-cancer drugs targeting AURKA (e.g. Alisertib) are recently considered as potential therapeutic options [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, anti-cancer drugs targeting AURKA (e.g. Alisertib) are recently considered as potential therapeutic options [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the phase 2 study by Haddad et al., 162 91 patients who had previously received ET and CDK4/6i were treated with alisertib alone or in combination with fulvestrant. For alisertib monotherapy, ORR was 20%, 24‐week CBR was 41%, and median PFS was 5.6 months; all similar to the combination where ORR was 20%, CBR was 29% and median PFS was 5.4 months 162 . The correlative analyses published with this study are based solely on ER and AURKA expression in pre‐treatment biopsies, where a positive AURKA expression was significantly associated with a shorter PFS in the monotherapy arm but not in the combination arm, and with additional studies underway 162 .…”
Section: G2/m Phase Transitionmentioning
confidence: 99%
“… 159 , 160 In the first phase 2 study, alisertib monotherapy demonstrated a manageable safety profile in a cohort of 53 BC patients, with an ORR of 18% in HR + or HER2 + BC patients resistant to ET, but minimal activity in TNBC. 161 In the phase 2 study by Haddad et al., 162 91 patients who had previously received ET and CDK4/6i were treated with alisertib alone or in combination with fulvestrant. For alisertib monotherapy, ORR was 20%, 24‐week CBR was 41%, and median PFS was 5.6 months; all similar to the combination where ORR was 20%, CBR was 29% and median PFS was 5.4 months.…”
Section: G2/m Phase Transitionmentioning
confidence: 99%
“…In SMARCA4-deficient tumor cells, the activity of AURKA is necessary for mitotic spindle assembly and cell survival, and it has been demonstrated that the AURKA inhibitor (VX-680) induces tumror cells death in vitro and in mouse vivo assays [ 51 ]. Shi [ 52 ] found that AURKA was a potential lung cancer marker by KEGG and GO enrichment analysis, and Alisertib has shown promising clinical activity in solid tumors [ 53 ].…”
Section: Therapy Strategiesmentioning
confidence: 99%